Shape‐Stabilized Phase Change Materials Based on Stearic Acid and Mesoporous Hollow SiO2 Microspheres (SA/SiO2) for Thermal Energy Storage. Issue 14 (13th April 2017) - Fan, Shuang; Gao, Hongyi; Dong, Wenjun; Tang, Jia; Wang, Jingjing; Yang, Mu; Wang, Ge
Abstract : The development of solar energy conversion and storage technologies has been attracting considerable attention in recent years. In this paper, a novel shape‐stabilized phase change material (SSPCM) based on stearic acid (SA) and mesoporous hollow SiO2 microspheres (SA/SiO2 ) was synthesized by an impregnating method. The mesoporous silica microspheres with an additional hollow cavity not only provide high loading capacity but also favor the free crystallization of SA, which is confined in the hollow microspheres by interfacial interaction and capillary action. There is no leakage from the obtained SSPCMs even if the temperature exceeds the melting point of SA. The SA/SiO2 PCM with 70 wt.‐% of SA exhibits high latent heat (reaching up to 135.3 J g –1 ), and its related thermal conductivity is 0.56 W mK –1, which was enhanced by 56 % relative to that of pure SA. Moreover, the SA/SiO2 composites show excellent thermal stability, which is beneficial for latent heat thermal energy storage (LHTES). Abstract : A novel shape‐stabilized phase change material (SSPCM) based on stearic acid (SA) and mesoporous hollow SiO2 microspheres (SA/SiO2 ) was synthesized by an impregnating method. The hollow cavity of the mesoporous hollow SiO2 microspheres can favor the free crystallization of SA, and the leakage of SA is prevented by the mesoporous shell.